KORELASI KADAR UNSUR HARA DAUN KELAPA SAWIT TERHADAP KADAR MINYAK SAWIT MENTAH - Ika Ucha Pradifta Rangkuti; Mardiana Wahyuni (Jurnal Agro Estate, 2019)
Mesocarp or fruit flesh is the main component of the cultivation of oil palm which is extracted to Crude Palm Oil (CPO). The amount of CPO produced from processing in palm oil mills is influenced by the quality of Fresh Fruit Bunches (FFB). Some factors that influence the quality of FFB are the type of crossing, plant age, maintenance level and fraction of fruit maturity. Adequacy of nutrients N, P, K, and Mg play a role in fruit formation and are expected to increase levels of CPO. In connection with this matter, research on the relationship / nutrient correlation with CPO content is needed. This research was conducted in October 2017 - March 2018 in the field with land suitability classes S1 (Maradja Hill), S2 (Limau Mungkur), S3 (Bah Birung Ulu) and STIPAP LPP Medan Practice Gardens. Processing data with single and multiple linear regression. Leaf samples were analyzed with the Sochlet apparatus in STIPAP Processing Laboratory. In general, the average nutrient content of leaves N, P, K were the normal category and nutrient Mg, Cl were deficiency category. The level of CPO (oil / mesocarp) varies from 31.14% - 59.59%. With single nutrient regression N, P, K, Cl has a positive correlation with CPO levels while Mg is negatively correlated. Multiple regression analysis of nutrient N, P, K, Mg and Cl has significant effect on O / N with a correlation coefficient of 0.744.